Follicular-phase endometrial scratching: a truncated randomized controlled trial. Issue 5 (6th May 2020) - Mackens, S; Racca, A; Van de Velde, H; Drakopoulos, P; Tournaye, H; Stoop, D; Blockeel, C; Santos-Ribeiro, S
Abstract: STUDY QUESTION: Does intentional endometrial injury (scratching) during the follicular phase of ovarian stimulation (OS) increase the clinical pregnancy rate (CPR) in ART? SUMMARY ANSWER: CPR did not vary between the endometrial injury and the control group, but the trial was underpowered due to early termination because of a higher clinical miscarriage rate observed in the endometrial injury arm after a prespecified interim analysis. WHAT IS KNOWN ALREADY: Intentional endometrial injury has been put forward as an inexpensive clinical tool capable of enhancing endometrial receptivity. However, despite its widespread use, the benefit of endometrial scratching remains controversial, with several recent randomized controlled trials (RCTs) being unable to confirm its added value. So far, most research has focused on endometrial scratching during the luteal phase of the cycle preceding the one with embryo transfer (ET), while only a few studies investigated in-cycle injury during the follicular phase of OS. Also, the persistence of a scratch effect in subsequent treatment cycles remains unclear and possible harms have been insufficiently studied. STUDY DESIGN, SIZE, DURATION: This RCT was performed in a tertiary hospital setting between 3 April 2014 and 8 October 2017. A total of 200 women (100 per study arm) undergoing IVF/ICSI in a GnRH antagonist suppressed cycle followed by fresh ET were included. PARTICIPANTS/MATERIALS, SETTING, METHODS: Participants were randomized with a 1:1 allocation ratio to either undergo a pipelle endometrial biopsy between Days 6 and 8 of OS or to be in the control group. The primary outcome was CPR. Secondary outcomes included biochemical pregnancy rate, live birth rate (LBR), early pregnancy loss (biochemical pregnancy losses and clinical miscarriages), excessive procedure pain/bleeding and cumulative reproductive outcomes within 6 months of the study cycle. MAIN RESULTS AND THE ROLE OF CHANCE: The RCT was stopped prematurely by the trial team after the second prespecified interim analysis raised safety concerns, namely a higher clinical miscarriage rate in the intervention group. The intention-to-treat CPR was similar between the biopsy and the control arm (respectively, 44 versus 40%, P = 0.61, risk difference = 3.6 with 95% confidence interval = −10.1;17.3), as was the LBR (respectively, 32 versus 36%, P = 0.52). The incidence of a biochemical pregnancy loss was comparable between both groups (10% in the intervention group versus 15% in the control, P = 0.49), but clinical miscarriages occurred significantly more frequent in the biopsy group (25% versus 8%, P = 0.032). In the intervention group, 3% of the patients experienced excessive procedure pain and 5% bleeding. The cumulative LBR taking into account all conceptions (spontaneous or following ART) within 6 months of randomization was not significantly different between the biopsy and the control group (54% versus 60%, respectively, P = 0.43). LIMITATIONS, REASONS FOR CAUTION: The trial was stopped prematurely due to safety concerns after the inclusion of 200 of the required 360 patients. Not reaching the predefined sample size implies that definite conclusions on the outcome parameters cannot be drawn. Furthermore, the pragmatic design of the study may have limited the detection of specific subgroups of women who may benefit from endometrial scratching. WIDER IMPLICATIONS OF THE FINDINGS: Intentional endometrial injury during the follicular phase of OS warrants further attention in future research, as it may be harmful. These findings should be taken in consideration together with the growing evidence from other RCTs that scratching may not be beneficial. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by 'Fonds Wetenschappelijk Onderzoek' (FWO, Flanders, Belgium, 11M9415N, 1524417N). None of the authors have a conflict of interest to declare with regard to this study.